Real-Time IoT-Based Wireless Interaction System for Patients with Disabilities - Rahman, Mahfujur (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2025)
The increasing population of disabled patients in hospitals highlights the critical need for solutions that address their unique and timely healthcare requirements. Traditional methods, such as employing full-time caregivers or implementing round-the-clock monitoring systems, are often costly and require substantial resources. This study presents a cost-efficient and real-time solution designed to enhance communication between nurses and multiple patients using a motion-based wireless interaction system. The system incorporates a mechanism for monitoring blood oxygen levels and heart rate alongside a motion-based messaging component. It utilizes the MAX30100 sensor module (Pulse Oximeter and Heart Rate sensor), MPU6050 sensor (Accelerometer and Gyroscope), and ESP8266 NodeMCU. These devices are mounted on a movable part of the patient’s body to enable efficient communication. Wireless messages are sent to a central receiver located at the nurse’s station, displayed on a screen, and supported by auditory alerts to ensure timely responses. Repeaters are employed to maintain seamless communication for wards located over 40 meters away, ensuring broader coverage. This system significantly lowers manpower demands and operational expenses while improving patient satisfaction and healthcare quality through automated caretaking and consistent monitoring. The design and architecture underwent comprehensive testing at different stages, culminating in a fully functional prototype. This innovative system addresses the challenges of continuous patient monitoring, providing a scalable and effective solution to advance healthcare services for disabled patients.